TI_GERICHTE 12.2015.14 vom 20. Juli 2015 , Riconoscimento ed exequatur di sentenza staniera - provvisionale ex art. 539 CPP/It - TI Tribunale d'appello (2015)
Riconoscimento ed exequatur di sentenza staniera - provvisionale ex art. 539 CPP/It